1995
DOI: 10.1007/bf01710057
|View full text |Cite
|
Sign up to set email alerts
|

Response to a booster dose 18 months after a low anti-HBs response (10–99 IU/l) to three doses of intradermally or intramuscularly administered recombinant hepatitis B vaccine

Abstract: The response to a booster dose, given by the same route 18 months after the completion of the primary vaccination scheme, was studied in hospital staff members who responded with anti-HBs levels in the range of 10-99 IU/l after three intradermal (i.d., n = 51) or intramuscular (i.m., n = 11) doses of recombinant hepatitis B virus (HBV) vaccine administered at 0, 1 and 6 months. At the time of boostering the anti-HBs levels had declined to < 10 IU/l in 44/51 (86%) of the i.d. and 10/11 of the i.m. vaccines. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Research in Europe and the USA has demonstrated that subjects who appear unresponsive or minimally responsive to the primary three‐dose hepatitis B vaccination account for 5–15% of vaccinees 22,23 . However, these individuals are not necessarily absolute non‐responders: the majority can develop protective levels of anti‐HBs after additional hepatitis B vaccination, consisting of a fourth or fifth dose, or an additional complete course of vaccination 21,24,25 . Administration of these additional doses of vaccine to low‐level or non‐responders can, in most cases, result in adequate antibody response and immunological priming 6 .…”
Section: Non‐respondersmentioning
confidence: 99%
“…Research in Europe and the USA has demonstrated that subjects who appear unresponsive or minimally responsive to the primary three‐dose hepatitis B vaccination account for 5–15% of vaccinees 22,23 . However, these individuals are not necessarily absolute non‐responders: the majority can develop protective levels of anti‐HBs after additional hepatitis B vaccination, consisting of a fourth or fifth dose, or an additional complete course of vaccination 21,24,25 . Administration of these additional doses of vaccine to low‐level or non‐responders can, in most cases, result in adequate antibody response and immunological priming 6 .…”
Section: Non‐respondersmentioning
confidence: 99%
“…Among medical students immunized id with 2 µg of plasma-derived vaccine, 63% and 85% had ≥ 10 mIU of anti-HBs/ml 30 and 20-24 months after primary immunization, respectively [9,10]. Struve et al [11] reported that seroconversion could be achieved in 50% of nonresponders to primary three doses (0, 1 and 6 months) im or id with an additional 1 to 2 doses by the same route as the initial vaccination.They also reported that 86% of the id vaccinees had anti-HBs below 10 IU/l after 18 months and 90% of them had increased to protective levels with a booster dose [12]. We administered additional doses to reassure protective immunity in those medical students with nonprotective titers after the primary doses.…”
Section: Discussionmentioning
confidence: 81%
“…The inconveniences of the patients (the risk of allergic reactions and other adverse effects as fatigue and myalgia) and the low risk of acquiring hepatitis B in Sweden (less than 10 cases/100 000 inhabitants per year 1990-94) (17) questions the necessity of hepatitis B vaccination in Swedish dialysis patients. So do the low rate of success, the low levels of response shown by us and others as well as a low persistence in time of antibodies in low level antibody responders (30) and the expense of such programs. Renal patients have been shown to have a low persistence of antibodies also with vaccine to pneumococci (31).…”
Section: Discussionmentioning
confidence: 91%